Mindful parenting in responding to social change: An analysis of Tafsir Al-Mishbah on Qur'anic parenting verses - Avina Amalia Mustaghfiroh (Societa: Journal of Society and Change, 2026)
Social change characterized by digitalization, individualization, and shifting values has created new challenges for parenting, while studies on mindful parenting remain predominantly grounded in psychological perspectives and have rarely been examined through Qur'anic exegesis. This study aims to analyze the concept of mindful parenting from the perspective of Tafsir Al-Mishbah and examine its relevance to contemporary social change. A qualitative approach employing the thematic (mawḍūʿī) interpretation method was applied to Q.S. Al-Nisāʾ [4]:9, Q.S. Al-Taḥrīm [66]:6, and Q.S. Luqmān [31]:13, 16, and 17. These verses were analyzed through Tafsir Al-Mishbah and synthesized with theories of mindful parenting and social change. The findings identify five core concepts: mindful communication, compassion, parental responsibility, spiritual awareness, and role modeling with self-regulation. Collectively, these concepts constitute an adaptive parenting paradigm for responding to contemporary social change while extending mindful parenting scholarship through the integration of Qur'anic exegesis, psychology, and sociology. Abstrak Perubahan sosial yang ditandai oleh digitalisasi, individualisasi, dan pergeseran nilai menghadirkan tantangan baru dalam praktik pengasuhan, sementara kajian mindful parenting masih didominasi oleh perspektif psikologi dan belum banyak dikaji melalui tafsir Al-Qur'an. Penelitian ini bertujuan menganalisis konsep mindful parenting dalam perspektif Tafsir Al-Mishbah serta menjelaskan relevansinya terhadap perubahan sosial kontemporer. Penelitian ini menggunakan pendekatan kualitatif dengan metode tafsir tematik (mawḍūʿī) terhadap QS. Al-Nisāʾ [4]:9, QS. Al-Taḥrīm [66]:6, serta QS. Luqmān [31]:13, 16, dan 17 yang dianalisis melalui Tafsir Al-Mishbah dan disintesiskan dengan teori mindful parenting serta teori perubahan sosial. Hasil penelitian mengidentifikasi lima konsep utama, yaitu komunikasi berkesadaran, kasih sayang, tanggung jawab orang tua, kesadaran spiritual, serta keteladanan dan pengendalian diri. Kelima konsep tersebut membentuk paradigma pengasuhan yang adaptif terhadap perubahan sosial sekaligus memperluas kajian mindful parenting melalui integrasi perspektif tafsir, psikologi, dan sosiologi.